Dengue Non-structural Protein 5 Polymerase Complexes With Promyelocytic Leukemia Protein (PML) Isoforms III and IV to Disrupt PML-Nuclear Bodies in Infected Cells - Giovannoni, Federico; Ladelfa, María Fatima; Monte, Martin; Jans, David A.; Hemmerich, Peter; García, Cybele (Frontiers in Cellular and Infection Microbiology, 2019)
Dengue virus (DENV) threatens almost 70% of the world’s population, with no therapeutic currently available. The severe, potentially lethal forms of DENV disease (dengue hemorrhagic fever/dengue shock syndrome) are associated with the production of high level of cytokines, elicited as part of the host antiviral response, although the molecular mechanisms have not been fully elucidated. We previously showed that infection by DENV serotype 2 (DENV2) disrupts promyelocytic leukemia (PML) gene product nuclear bodies (PML-NBs) after viral protein translation in infected cells. Apart from playing a key role as the nucleating agent in forming PML-NBs, PML has antiviral activity against various viruses, including DENV. The present study builds on this work, showing for the first time that all four DENV serotypes elicit PML-NB breakdown. Importantly, we show for the first time that of the nuclear localizing proteins of DENV, DENV nonstructural protein (NS) 5 polymerase alone is sufficient to elicit PML-NB disassembly, in part through complexing with PML isoforms III and IV, but not other PML isoforms or other PML-NB components. The results raise the possibility that PML-NB disruption by nuclear localized NS5 contributes to DENV’s suppression of the host antiviral response.